2001
DOI: 10.1111/j.1749-7345.2001.tb01101.x
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Performance of Male Argentine Red Shrimp Pleoticus muelleri Bate (Decapoda, Penaeoidea) in Culture Conditions

Abstract: Spermatophore and sperm quality of male Argentine red shrimp Pleoticus muelleri held under laboratory conditions was evaluated using compound spermatophore weight, sperm count and percentage of live sperm as indicators. Thirty‐seven males of S to 20 g wet weight were held indoors in a 3‐m diameter circular fiberglass tank for 45 d. They were fed fresh squid, clam and pelletized diet. Spermato‐phores were obtained by manual ejaculations. Four shrimps were re‐ejaculated to verify the subsequent spermatophore reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 28 publications
0
3
1
Order By: Relevance
“…As concerns the sperm count, no differences between brownish and normal spermatophores were found in C. quadricarinatus, as in P. muelleri (Díaz et al, 2001) and L. vannamei (Diamond et al, 2008), in contrast to the results reported by Chamberlain et al (1983) and Pascual et al (1998) for L. setiferus, L. vannamei and P. stylirostris. Under light microscope magnification, we did not observed abnormal sperm as was reported for L. vannamei (Dougherty and Dougherty, 1989;Diamond et al, 2008) and L. setiferus (Talbot et al, 1989).…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…As concerns the sperm count, no differences between brownish and normal spermatophores were found in C. quadricarinatus, as in P. muelleri (Díaz et al, 2001) and L. vannamei (Diamond et al, 2008), in contrast to the results reported by Chamberlain et al (1983) and Pascual et al (1998) for L. setiferus, L. vannamei and P. stylirostris. Under light microscope magnification, we did not observed abnormal sperm as was reported for L. vannamei (Dougherty and Dougherty, 1989;Diamond et al, 2008) and L. setiferus (Talbot et al, 1989).…”
Section: Discussioncontrasting
confidence: 64%
“…Among other factors, it has been demonstrated that diseases affect the reproductive system, decreasing the reproductive performance. The darkening of the spermatophore, also named melanisation, was found in the reproductive system of males of the penaeid shrimps Litopenaeus setiferus Bray et al, 1985;Brown et al, 1979;Chamberlain et al, 1983;LeungTrujillo and Lawrence, 1987;Pascual et al, 1998;Rosas et al, 2004;Talbot et al, 1989), Litopenaeus vannamei (Alfaro and Lozano, 1993;Chamberlain et al, 1983;Diamond et al, 2008;Dougherty and Dougherty, 1989;Parnes et al, 2006;Perez Velazquez et al, 2001), Penaeus stylirostris (Chamberlain et al, 1983) and Pleoticus muelleri (Díaz et al, 2001), and in the caridean shrimp Macrobrachium rosenbergii (Harris and Sandifer, 1986). It is characterised by a reduction in sperm count and sperm viability leading to male infertility (Chamberlain et al, 1983;Leung-Trujillo and Lawrence, 1987;Pascual et al, 1998;Rosas et al, 2004 for revision).…”
Section: Introductionmentioning
confidence: 99%
“…The few studies of redclaw males that have been reported examined the structural changes during the formation of spermatophore and after the extrusion, and the eyestalkandrogenic gland-testis endocrine axis (Khalaila et al, 1999;Khalaila et al, 2002;Greco et al, 2007;Greco and Lo Nostro, 2008;Ding et al, 2009). There have been discernibly fewer studies that have examined the morphology and ultrastructure of the male reproductive system and spermatogenesis of freshwater crayfishes compared to the substantial literature addressing economically important crabs (Shangguan and Li, 1994;Du et al, 1999;Sainte Marie and Sainte Marie, 1999;Hobbs, Jr., et al, 2007) and shrimps (Lynn and Clark Jr., 1983;Zhao et al, 1997;Díaz et al, 2001;Akarasanon et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The reproductive performance of shrimp is influenced by many factors including the size of the broodstock and its habitat [6], cultivation systems and environmental conditions [2,[7][8][9], season and age [10], diet [11,12], and genetics [13]. Studies on some of the factors that influence the reproductive performance of RCS have been carried out, including those affecting diet [14,15] and temperature [16,17].…”
Section: Introductionmentioning
confidence: 99%